Four charming spells - Cahoon, Lynn (Cahoon, Lynn. Kitchen witch mysteries, 2023)
"When tea shop owner and local coven member Mahogany Medford asks her to look into her mother's untimely death, caterer and witchcraft trainee Mia stirs the pot as she, with Gran's protective stone and a circle of trusted confidants, seeks to find the truth"--